2017
DOI: 10.1371/journal.pone.0176981
|View full text |Cite
|
Sign up to set email alerts
|

How regularity representations of short sound patterns that are based on relative or absolute pitch information establish over time: An EEG study

Abstract: The recognition of sound patterns in speech or music (e.g., a melody that is played in different keys) requires knowledge about pitch relations between successive sounds. We investigated the formation of regularity representations for sound patterns in an event-related potential (ERP) study. A pattern, which consisted of six concatenated 50 ms tone segments differing in fundamental frequency, was presented 1, 2, 3, 6, or 12 times and then replaced by another pattern by randomly changing the pitch of the tonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
36
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(43 citation statements)
references
References 78 publications
5
36
2
Order By: Relevance
“…Indeed, a study published in 2017 found evidence that even in the absence of direct attention unfamiliar short melodic patterns are extracted when learning has to rely solely on relative pitch cues because absolute pitch information varies due to transpositions of these patterns [ 17 ]. In naïve listeners that performed a loudness change detection task, Bader and colleagues [ 17 ] observed a clear mismatch-negativity (MMN) in response to the introduction of a new pattern not only after previous exact (i.e. absolute) pattern repetitions but also when the previous pattern was transposed (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, a study published in 2017 found evidence that even in the absence of direct attention unfamiliar short melodic patterns are extracted when learning has to rely solely on relative pitch cues because absolute pitch information varies due to transpositions of these patterns [ 17 ]. In naïve listeners that performed a loudness change detection task, Bader and colleagues [ 17 ] observed a clear mismatch-negativity (MMN) in response to the introduction of a new pattern not only after previous exact (i.e. absolute) pattern repetitions but also when the previous pattern was transposed (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…MMN is considered to reflect the outcome of a process where a deviant event is found incongruent with “the predictions produced by the neural representations of regularities extracted from the acoustic environment” [ 16 ]. Bader et al [ 17 ] observed that MMN was elicited after only three presentations of the preceding pattern and at a similar latency in both absolute and relative pitch contexts. Bader et al [ 17 ] interpreted this as strong indication that the sensory memory trace forms automatically and violations of complex pattern regularities are extracted even without absolute pitch cues.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations